Railroads as anthropogenic dispersal corridors. Possible way of the colonization of Poland by a common wall lizard (Podarcis muralis, Lacertidae) - Dudek, Krzysztof (Ecological Questions, 2015)
The common wall lizard is a new lacertid species in the Polish herpetofauna. However, the discovered populations seem to be introduced. In this article, I intend to describe a possible way of lizards dispersal through railways. I suppose that the common wall lizard may colonize new areas by freight trains as an incidental cargo from quarries they inhabit.